2018
DOI: 10.1371/journal.pone.0206002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between birth weight to placental weight ratio and major congenital anomalies in Japan

Abstract: Recent studies have indicated that birth weight to placental weight (BW/PW) ratio is related to perinatal outcomes, but the effect of congenital abnormalities on BW/PW ratio remains unclear. We performed this study to elucidate correlations between BW/PW ratio and congenital abnormalities. Subjects were 735 singleton infants born at 34–41 weeks of gestation admitted to our center between 2010 and 2016. Of these, 109 infants (15%) showed major congenital anomalies. Major congenital anomalies and subgroups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In addition, the highest quintile of birth weight to placental weight ratio was associated with higher uterine artery Doppler mean pulsatility index and umbilical artery Doppler pulsatility index later in gestation 23 . Major congenital anomalies have been linked to higher (> 90th) percentiles of birth-weight-to-placental-weight ratio 83 . The impact of altered placental morphometry during pandemic on infant neurodevelopmental outcomes merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the highest quintile of birth weight to placental weight ratio was associated with higher uterine artery Doppler mean pulsatility index and umbilical artery Doppler pulsatility index later in gestation 23 . Major congenital anomalies have been linked to higher (> 90th) percentiles of birth-weight-to-placental-weight ratio 83 . The impact of altered placental morphometry during pandemic on infant neurodevelopmental outcomes merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that the ratio of human newborn to placental weight may be related to perinatal changes; a higher ratio indicates insufficient oxygen to the fetus and a lower ratio suggests a suboptimal fetal condition 45 , 46 . In the study by Denomme et al senile male mice were found to have a higher fetal: placental weight ratio compared to their youth 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Results of the present study indicate that senile males present a decrease in reproductive performance. In consonance, in humans, paternal age can be associated with increased prevalence of comorbid conditions of urological character (decrease sperm motility, percentage of normal sperm morphology, sperm concentration, and increased sperm DNA fragmentation and ejaculatory dysfunction) 49 51 , which affect reproductive potential, fertility 46 , low conception rates to poor offspring health 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Placental morphology was significantly associated with placental function, and abnormal placental morphological indicators were related with the increased risk of pregnancy complications (17,18). In previous studies, limited studies have focused on the effect of maternal TPOAb presence on placental morphology during pregnancy and findings were controversial (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%